2016
DOI: 10.1098/rstb.2015.0441
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary transitions during RNA virus experimental evolution

Abstract: One contribution of 13 to a theme issue 'The major synthetic evolutionary transitions'. In their search to understand the evolution of biological complexity, John Maynard Smith and Eörs Szathmáry put forward the notion of major evolutionary transitions as those in which elementary units get together to generate something new, larger and more complex. The origins of chromosomes, eukaryotic cells, multicellular organisms, colonies and, more recently, language and technological societies are examples that clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…This 6 suggests the action of genetic drift, rather than positive selection, leading to a change in the 7 frequency of the two genotypes in the different subpopulations. 8 Similar to the patterns observed for BGMV, a clear geographical segregation was 9 also observed for both EuYMV components, with only minor differences in the assignment 10 of some DNA-A and DNA-B components to the three genetic clusters (South-1, South-2 11 and GO) ( Figure 3). 12 Although it was not possible to define clear genetic clusters for MaYSV DNA-B 13 components based on DAPC analysis, the DNA-A components were split into four groups 14 ( Figure 3).…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…This 6 suggests the action of genetic drift, rather than positive selection, leading to a change in the 7 frequency of the two genotypes in the different subpopulations. 8 Similar to the patterns observed for BGMV, a clear geographical segregation was 9 also observed for both EuYMV components, with only minor differences in the assignment 10 of some DNA-A and DNA-B components to the three genetic clusters (South-1, South-2 11 and GO) ( Figure 3). 12 Although it was not possible to define clear genetic clusters for MaYSV DNA-B 13 components based on DAPC analysis, the DNA-A components were split into four groups 14 ( Figure 3).…”
Section: Introductionsupporting
confidence: 74%
“…For the DNA-A, two 5 major clades were well supported, with isolates sampled in Rio Grande do Sul (RS) and 6 Paraná states (PR) clustered separately from those sampled in Góias (GO) and Mato Grosso 7 do Sul (MS). The same clusters could be observed in the DNA-B tree, except that isolates 8 sampled in MS clustered with those from RS and PR, suggesting a reassortment event. 9 Due to the complex recombination profile of the MaYSV data set (see below), DNA- 10 A and DNA-B phylogenetic trees showed a high degree of incongruence and displayed no 11 obvious pattern of segregation ( Figure 2D).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…We showed that the egfp-tagged viruses replicated in the injected pupae increased their loads thousands of times (Figure 2, Figure 7C) suggesting that even a non-essential gene in an RNA virus genome could be relatively stable ( Figure 7C). It is a widely accepted view, that gene exchanges between different virus groups and incorporation of host mRNA or their fragments occur during the RNA virus evolution [40,41]. It is necessary for these foreign inserts to be present in genomic RNA undergoing several rounds of replication events to allow further adjustment to the viral RNA genome context via mutagenesis.…”
Section: Discussionmentioning
confidence: 99%